Pendampingan Penyaluran Zakat pada Para Peternak Lebah Madu di Desa Joho Kediri - Ahmad Muthi' Uddin; Gusti Ramadani; Moh. Miftahul Choiri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
An in-depth study of the perspective of beekeepers in the Village Joho towards zakat becomes very urgent. Because in general research about honey zakat only tends to the naqli arguments and ijtihad of the scholars without involving the farmers themselves who in this case are the main actors in honey zakat. From the description above, it can be formulated the research problem as: the following (1) How is the process and management of honey in Joho Village? (2) How the perspective of beekeepers on the obligation of zakat honey in Joho Village? This type of research is qualitative with a phenomenological approach. Source primary data, namely honey farmers in Joho Village with data collection in the form of in-depth interviews, observations and documentation which are then analysis using data codification, data presentation, and withdrawal methods conclusion/verification. The results of the study, namely (1) the process and governance in producing honey for beekeepers is by looking at the weather conditions. Because weather conditions have serious consequences on bee stamina and flower growth, where these two things affect the scale of honey income for farmers bee. (2) two according to the perspective of the honey beekeeper community in Joho . Village that, the obligation of zakat honey is considered not an obligation that must be carried out. They consider honey is not something that must be zakat. However, the habit that occurs there is that the breeders give part of the honey harvest to the local community. The gift considered as a form of gratitude for the harvest obtained. There the farmers The majority of Joho Village honey distributes their harvested honey when the results are abundant, so the concept is alms.